Supplemental periodontal regeneration by vertical ridge augmentation around dental implants. A preclinical in vivo experimental study. Issue 11 (18th September 2019) - Lee, Changseok; Kim, Sungtae; Kim, Junhwan; Namgung, Dajeong; Kim, Kyounghwa; Ku, Young
Abstract: Objectives: To evaluate the supplemental periodontal regeneration on adjacent teeth by vertical ridge augmentation around dental implants. Material and methods: The second premolar and the fourth premolar were extracted from both sides of the mandible in four beagle dogs. After 2 months, defects of 3 mm and 5 mm deep were formed. In the test group, vertical ridge augmentation was performed around a dental implant, and in the control group, vertical ridge augmentation was performed without implant placement. The animals were euthanized 3 months after the procedure, and radiographic and histomorphometric analyses were performed. Results: Overall, the test group showed better results than the control group. The presence of new cementum in the histological examination of the test group confirmed that vertical ridge augmentation with proper space maintaining could contribute to periodontal regeneration of adjacent teeth. Statistically significant difference in new bone height (%) was found in group I (5‐mm defect depth and implant placement, GBR) when compared with group III (5‐mm defect depth, GBR) and IV (3‐mm defect depth, GBR). New bone area (%) was statistically different between groups I and IV. Conclusions: In conclusion, within the limitation of this study using mandibular residual ridges after extraction of a single tooth in dogs, grafted space was maintained by dental implants better in the deep defect (5‐mm depth) than the shallow defect (3‐mm depth). Vertical ridge augmentation around dental implants also promoted neighboring periodontal regeneration.